2007
DOI: 10.5194/angeo-25-2045-2007
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation at Concordia station (Antarctica) and its dependence on IMF conditions

Abstract: Abstract.After some short test surveys, during the 2004-2005 summer expedition in Antarctica, a geomagnetic French-Italian observatory was installed on the plateau (geographic coordinates: 75.1 • S, 123.4 • E; corrected geomagnetic coordinates: 88.9 • S, 54.3 • E; UT=LT−8) very close to the geomagnetic pole. In this paper we present some peculiarities of the daily variation as observed at this polar cap observatory during the years 2005 and 2006, taking into account the different Loyd seasons and different int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Consistent with this scenario, our analysis has shown that at DMC, i.e. close to the geomagnetic pole, the diurnal variation for negative B y is larger and the curve is shifted to earlier times by about 3 h with respect to positive B y (see also Cafarella et al, 2007). It is interesting that these features do not appear at the stations at lower geomagnetic latitude (there is just some tendency to a slight time shift, more evident for the Y component, at TNB), indicating that the IMF orientation contributes differently at various positions within the polar cap.…”
Section: Figuresupporting
confidence: 69%
“…Consistent with this scenario, our analysis has shown that at DMC, i.e. close to the geomagnetic pole, the diurnal variation for negative B y is larger and the curve is shifted to earlier times by about 3 h with respect to positive B y (see also Cafarella et al, 2007). It is interesting that these features do not appear at the stations at lower geomagnetic latitude (there is just some tendency to a slight time shift, more evident for the Y component, at TNB), indicating that the IMF orientation contributes differently at various positions within the polar cap.…”
Section: Figuresupporting
confidence: 69%
“…Daily variation as observed at Italian polar geomagnetic observatories, was described in previous works by Cafarella et al (1998), Lepidi et al (2003), Cafarella et al (2007a) and Santarelli et al (2007a). In one of them the study of daily variation, as observed at TNB observatory through fourteen years of data, showed a pronounced seasonal effect on the amplitude of the signal but not on its pattern.…”
Section: Julian Days 2006supporting
confidence: 68%
“…The jump of dF in the range March 1mid-September 2007 is due to a move of the sensor of the scalar magnetometer. Regarding the daily variations, we refer to the work published by Cafarella et al (2007) which describes some peculiarities of this variation in connection with IMF conditions. Figures 9 and 10 highlight clearly the seasonal variation due to large variation of the ionospheric conductivity controlled by the solar radiation.…”
Section: Magnetic Field Daily Meansmentioning
confidence: 99%
“…The data collected within these three first years of permanent opening show that it makes sense to deploy an observatory on the ice cap despite the potential disturbances which might be caused by the ice drift and despite the unusual environmental conditions. It is too early to evaluate the impact of these data on the knowledge of the internal and external Earth's field, although some preliminary studies have already shown their importance (Lepidi et al, 2003;Cafarella et al, 2007). This paper focuses on the long-term field variation, whose validation is of prime importance for the internal field knowledge, but we have to mention the collection of the one second data, not yet worked out.…”
Section: Future Improvements and Conclusionmentioning
confidence: 99%